Green port development in Hong Kong - reduction of marine and port-related emissions - Wong, EYC; Lau, HYK (Hang Seng Management College., 2014)
The Conference proceedings' website is located at http://www.hsmc.edu.hk/images/scm_CallForPaper/Conference%20Proceedings.pdf The impact of air pollutant emissions from shipping and port operations towards environment and health is a pressing global concern. The marine and port sectors have contributed significantly to the growth of the supply chain industry and the economic development, while, at the same time, the pollutant emissions rising from ships and port-related operations have inflicted adverse public health concerns. Leading ports and terminals continuously impose measures to reduce the greenhouse gas emitted during vessel berthing. Hong Kong, being the third largest container port in the world and having the second cruise terminal running into operation, urgently requires comprehensive green port operations and practices. This paper evaluates and benchmarks the latest measures conducted by the leading ports over the world in reducing the greenhouse gas emissions from ship and port operations. International regulations, onshore power supply, vessel speed reduction, and fuel switching are analyzed. Recommendations on the future green port development in Hong Kong are proposed. postprint